Improving anti‐bullying laws and policies to protect youth from weight‐based victimization: parental support for action. Issue 2 (26th April 2016) - Puhl, R. M.; Suh, Y.; Li, X.
Summary: Background: Weight‐based bullying is a prevalent problem among youth with overweight and obesity, but remains neglected in existing policy‐level strategies to address youth bullying. Parental support is an influential catalyst motivating political will for policy decisions affecting youth, but has received limited research attention. Objectives: To assess levels of, and predictors of, parental support for school‐based policies and state/federal legal measures to address weight‐based bullying in 2014 and 2015. Methods: Identical online questionnaires were completed by two independent national samples of parents in 2014 and 2015 ( N  = 1804). Results: Parental support for all policy actions was high (at least 81%) and significantly increased from 2014 to 2015 for legal measures that would a) require state anti‐bullying laws to add protections against weight‐based bullying, and b) enact a federal anti‐bullying law that includes weight‐based bullying. Conclusions: These findings can inform policy discourse about remedies for youth bullying, and suggest that parental support for improved legal protections against weight‐based bullying is present, consistent, and strong.